Occurrence of Shigella, Yersinia and Salmonella species from selected wildlife and habitats in Sarawak - Chen, Yik Ming (Universiti Malaysia Sarawak (UNIMAS), 2012)
Shigella spp., Salmonella spp. and Yersinia spp. are gastrointestinal pathogens which can infect birds, bats, rodents and other small mammals. These animals may serve as reservoir for many diseases and play an important role in transmission of zoonoses. The destruction or disturbances of the wildlife habitats have been identified as a factor that lead to the emergence of these zoonoses outbreaks as habitats can influence the composition of bacterial species. Therefore, this study was conducted to determine the occurrence and association of Shigella spp., Salmonella spp. and Yersinia spp. in selected wildlife from two natural and three disturbed habitats., Three sampling trips to Nanga Merit, Pueh and Mount Singai were held for the samples collection in the study. These areas represented disturbed (Nanga Merit's village, Pueh and foot of Mount Singai) and natural habitats (Nanga Merit's forest and Mount Singai's forest). Anal or cloacal swabs, feacal and small intestinal of birds, bats and rodents were collected aseptically. In addition, soil and water samples were collected along the trapping routes to represent environmental samples. A total of 714 samples were collected from the animal and environment from the three sampling. XLD and CIN agar were used for the isolation of Shigella, Salmonella and Yersinia. Shigella, Salmonella and Yersinia were absent in all the animal and environmental samples collected from Pueh and Mount Singai. The isolated bacteria were then identified through a series of standard biochemical tests and multiplex PCR. Through multiplex PCR, virulence genes of Shigella (ipaH and ial) were detected in three bats and one bird sample from Nanga Merit Village which represent a disturbed habitat. One bird, two bats, a soil and a water sample from the forest in Nanga Merit which represent natural habitat were positive for the ipaH and ial gene. One bat isolate from both sites at Nanga Merit were positive for the flic gene which is a virulence gene in Salmonella Typhimurium. No Yersinia was found in any of the samples from all the sampling trips indicating none of the wild animals harboured Yersinia. Birds and bats from village showed higher percentage for the presence of virulence genes of Shigella spp. and Salmonella spp. compared to the forest in Nanga Merit. The Shigella isolates were sequenced and identified as Shigella boydii strain 3555-77. Two Salmonella strains which were positively detected for flic gene in bat samples were sequenced as Salmonella enteric subsp enteric serovar Typhimurium. The low occurrence of Shigella and Salmonella in birds and bats samples showed the low transmission risk of these pathogenic bacteria from human, animals and environment. The absence of Shigella, Yersinia and Salmonella species in soil and water indicate the low contamination of the bacteria through soil and water in Nanga Merit. Even though the number of isolates detected per species examined is low, the potential of infection risk of Shigella, Yersinia and Salmonella in the wildlife and environment had to be monitored to prevent infection in future.